Stabilizing Layered Structure in Aqueous Electrolyte via Dynamic Water Intercalation/Deintercalation. Issue 13 (18th February 2022) - Xue, Liang; Zhang, Qinghua; Huang, Yalan; Zhu, He; Xu, Lili; Guo, Shiying; Zhu, Xiaohui; Liu, Hanghui; Huang, Yin; Huang, Jiangfeng; Lu, Lude; Zhang, Shengli; et al.
Abstract: Aqueous lithium‐ion batteries (ALIBs) with nonflammable feature attract great attention for large‐scale energy storage. However, the layered cathode materials (such as LiCoO2 ) present serious capacity decay in ALIBs. The degradation mechanism of layered cathode materials in ALIBs is still not clear and an effective strategy to improve cycling stability remains a great challenge. In this work, the authors use LiCoO2 as a typical example to investigate its structural degradation in aqueous electrolytes. It is found that H + insertion accelerated irreversible layered‐to‐spinel phase transition is the main reason causing structural degradation and fast capacity fading in LiCoO2 . Subsequently, Li‐excess Li1+ t Co1− t O2− t with intermediate spin Co 3+ is developed to mitigate H + influence and the adverse phase transition in aqueous electrolyte. It is interesting to discover that reversible water intercalation/deintercalation occurs in the layered structure during charge/discharge, which effectively suppresses the layered‐to‐spinel phase transition with cycling. Benefiting from the stabilized layered structure, the Li‐excess Li1.08 Co0.92 O1.92 shows a significantly improved cycling performance in the neutral aqueous electrolyte with a large specific capacity and excellent rate capability. This work provides a promising structural regulation strategy for the layered cathode materials, enabling their potential application in ALIBs. Abstract : To stabilize the layered structure in aqueous electrolyte, Li‐excess Li1+ t Co1− t O2− t is developed to mitigate H + attack and the adverse phase transition. Li‐excess Li1+ t Co1− t O2− t provides open channels from (001) planes, enabling dynamic water intercalation/deintercalation in the layered structure. With reversible water intercalation/deintercalation, the layered structure is effectively stabilized in aqueous electrolyte, resulting in outstanding cycle performance in aqueous batteries.